Isolation and resistance test of several isolates of Lactobacillus in low pH - RIANI HARDININGSIH; ROSTIATI NONTA REFINA NAPITUPULU; TITIN YULINERY (Biodiversitas Journal of Biological Diversity, 2006)
Several isolates of Lactobacillus had been isolated from Indonesian fermented foods. Four isolates where isolated from tongcai (TT2), saguer drink (Sg.Mnd.N2), pindang ikan selar (PSl1) and sawi asin (S5) had been used in this research. The aim of the research was to get Lactobacillus isolates as probiotic candidate and to know its resistance to low pH. The treatment were several concentration of low pH of MRS broth medium, i.e. 2; 2.5; 3; and 6.5 (optimal pH). The optical density (OD) was measured after 24, 48, 72, and 96 hours respectively, with three replication by using spectrophotometer (Î» = 600 nm). The results showed that all Lactobacillus isolates (i.e. TT2, Sg.Mnd.N2, PSl1, and S5) could been used as probiotic candidate because they were resistant to all of low pH used. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: low pH, Lactobacillus, probiotic